Re-thinking non-core regions: planning strategies and practices beyond growth. Issue 2 (1st February 2018) - Leick, Birgit; Lang, Thilo
ABSTRACT: Periods of ongoing growth in the economy and demographics have come to a halt for many European regions for various reasons, challenging their economic development prospects. Despite the heterogeneous nature of stagnation, decline, peripheralization or even stigmatization to be found there, these configurations 'beyond growth' have in common that short-term 'fire-fighting' policy approaches aiming to foster regional economic growth face some important limitations. We argue that this has to do, among other things, with the overall direction of established and orthodox planning approaches that are predominantly based on growth-oriented paradigms and implicitly or explicitly work with dichotomous categories such as core–periphery and metropolitan versus non-metropolitan spaces; these do, however, not capture local realities in these cases. Using the notion of non-core regions, we plead for conceptualizing non-core regions and their regional economic development trajectories in different ways: thinking 'beyond growth'. Such alternative ideas should be informed by alternative understandings of growth, development and sustainability in order to influence theories and concepts, but also to support new approaches to planning practice. To this aim, we discuss non-core regions from a social constructivist perspective, elaborating some points of departure for conceptualizing and practising regional planning 'beyond growth'.